Evaluation of Egyptian cotton cultivars - M, Omar A; A, Mohamed A; M S, Abd EL-Aty; A, El-Akhedar A; A, Basyoni W (The Indian Journal of Agricultural Sciences, 2020)
Present study was carried out to evaluate 11 cotton varieties under two locations over two growing seasons 2015 and 2016 in Egypt. The results showed that there were significant differences among environment, genotypes, and their interactions for all the studied characters. The variety Giza 94 surpassed all varieties in yield and its components shared with the variety Giza 92 for seed cotton yield. The varieties Giza 94, Giza 92 and Giza 96 recorded highest yield and yield components at Nubariya location. The varieties Giza 87, Giza 88, Giza 92, Giza 93 and Giza 96 recorded highest values at Nubariya location for most fiber characters. Principal component analysis showed that the characters which have relatively high value in the first principal component (PC1) were earliness percentage, seed cotton yield, lint yield, boll weight, lint percentage, and micronaire reading. The second principal component (PC2) was principally affected by earliness percentage, fiber length and fiber strength. At the same time, cluster analysis could efficiently describe the characteristics of group of genotypes in different groups. The eleven cotton genotypes were grouped into five major clusters. The obtained results indicated the presence of genetic diversity among the tested cotton genotypes. Genotypes from divergent clusters can be used for hybridization in order to isolate useful recombinants in the segregating generations. This information might be used in the breeding programs for improvement of Egyptian cotton.